Empowering an Exemplary English Teacher’s Teaching Quality: The Holy Grail of Teacher Professional Development - Karim, Sayit Abdul; Hikmauli R., Taufan; Besma, Meindra; Matas, Gordan (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2025)
In the evolving education landscape, teacher professional development (TPD) is crucial for enhancing English language teaching. This qualitative study, using a case study approach, explored how TPD programs impact teaching quality, focusing on the experiences of NH, an exemplary female teacher at SMA N 1 Prambanan Klaten, Central Java. The data were collected through semi-structured interviews, and thematic analysis was employed to identify key insights. Data analysis in this study followed the three-stage framework developed by Miles et al. (1988): data reduction, data display, and conclusion drawing/verification, including; first, Data reduction aimed to simplify the raw data by summarizing key points and paraphrasing, thus making it more manageable. Second, Data display focused on organizing and presenting the reduced data for enhanced comprehension. Finally, conclusion drawing/verification involved interpreting the displayed data and deriving meaningful insights. The findings revealed that TPD programs, including the Teacher Educator Program, Teacher Target Program, and Instructor Mover Program, significantly contributed to the teacher's professional growth. Specifically, the teacher highlighted the benefits of collaborative learning, practical application of materials, active learning strategies, and the development of a strong professional community. These elements were perceived as essential for effective TPD. This study recommends future research to investigate diverse TPD approaches across various educational contexts and teacher demographics to further understand their impact on teaching quality. Keywords: Students Learning Outcome, Teaching Quality, Teacher Professional Development